Composition and origin of PM10 in Cape Verde: Characterization of long-range transport episodes. (February 2016) - Salvador, P.; Almeida, S.M.; Cardoso, J.; Almeida-Silva, M.; Nunes, T.; Cerqueira, M.; Alves, C.; Reis, M.A.; Chaves, P.C.; Artíñano, B.; Pio, C.
Abstract: A receptor modelling study was performed to identify source categories and their contributions to the PM10 total mass at the Cape Verde archipelago. Trajectory statistical methods were also used to characterize the main atmospheric circulation patterns causing the transport of air masses and to geographically identify the main potential source areas of each PM10 source category. Our findings point out that the variability of the PM10 levels at Cape Verde was prompted by the advections of African mineral dust. The mineral dust load was mainly composed by clay-silicates mineral derived elements (22% of the PM10 total mass on average) with lower amounts of carbonates (9%). A clear northward gradient was observed in carbonates concentration that illustrates the differences in the composition according to the source regions of mineral dust. Mineral dust was frequently linked to industrial emissions from crude oil refineries, fertilizer industries as well as oil and coal power plants, located in the northern and north-western coast of the African continent (29%). Sea salt was also registered in the PM10 mass during most part of the sampling period, with a lower impact in the PM10 levels than the mineral dust one (26%). Combustion aerosols (6%) reached the highest mean values in summer as a consequence of the emissions from local-regional sources. Biomass burning aerosols produced from October to November in sub-sahelian latitudes, had a clear influence in the content of elemental carbon (EC) recorded at Cape Verde but a small impact in the PM10 total mass levels. A minor contribution to the PM10 mass has been associated to secondary inorganic compounds-SIC. Namely, ammonium sulfate and nitrate (SIC 1–5%) and calcium sulfate and nitrate (SIC 2–3%). The main origin of SIC 1 was attributed to emissions of SO2 and NOx from industrial sources located in the northern and north-western African coast and from wildfires produced in the continent. SIC 2 had a clear regional origin in the summer period. However, in the winter period there were probably contributions of soil emissions of evaporate minerals from regions of eastern Algeria. The location of Cape Verde in the Atlantic Ocean at subtropical latitudes, and the absence of relevant local sources of anthropogenic atmospheric pollutants, becomes this archipelago, a perfect site to study the impact of external contributions on the background levels of PM10 registered over the north-eastern tropical Atlantic. Highlights: PM10 sources at Cape Verde were characterized by multiple receptor techniques. PM10 levels variability was prompted by advections of African mineral dust. Mineral dust was frequently mixed with industrial emissions from northern Africa. Wildfires occurring at the African continent contributed to the levels of EC. Marine air masses strongly influenced the PM10 background levels.